Authentic Inquiry in Science Education Between 2003 and 2023: A Bibliometric Analysis Use RStudio - Kerans, Geterudis; Sanjaya, Yayan; ‎ , Liliasari (KnE Social Sciences, 2024)
The primary aim of this study is to investigate scholarly literature about the utilization of authentic inquiry in the context of science education throughout the past two decades (2003–2023). Additionally, this analysis aimed to examine the collaborative efforts of authors, institutions, and nations in domains closely associated with this research. Thematic and keyword analyses were performed to discover the most current and up-to-date study topics. The present study reveals 271 scholarly articles about authentic inquiry in science education identified from the SCOPUS database. These articles were sourced from 128 distinct publications, which involved the collaborative efforts of 812 authors. The time frame for this analysis spanned from 2003 to 2023. The annual growth rate observed in this study was 2.98%. Furthermore, the average number of citations per document was 23.62, while the study included 12.479 references cited. In the current context, Yarden from the Weizmann Institute of Science is foremost among the authors, having authored four publications and amassed ninety citations. Furthermore, the aggregate quantity of papers written by individuals from the United States amounts to 116. In addition, Australia is identified as the second most significant contributor, having nine published publications. The theme analysis method is utilized to present a network of thematic keywords consisting of 50 keywords that have been identified as appearing at least four times throughout the text being examined. Based on the bibliometric analysis, the authors propose a need for further enhancement of authentic inquiry research in science education. Keywords: authentic inquiry, science education, bibliometric, RStudio